Nest and Nidification Activities of the Spoonbill Platalea leucorodia in Westerghat Region of Shimoga, Karnataka - Dayananda, G.Y.; Hosetti, B.B. (Our Nature, 2010)
Nest and nidification behaviour of the Spoonbill, Platlea leucorodia (Family- Threskiornithidae) was studied for three seasons during 2003-2005, at Gudavi Bird Sanctuary (GBS), Gudavi village, Sorab, Karnataka. The GBS harbored about 12 thousand birds of various species, of these, only 10-12 pairs of Spoonbills were breeds every year in this place. There were five Spoonbill nests, of which one was old egret nest and the four were newly built by Spoonbills. The clutch size was two to three in each nest (N = 5) and the shape of the egg was oval, white with small brown spots. The nesting activity usually starts in the month of late July and ends during December. The nesting activity, nest site selection, nesting habitat, nesting material, nest size, and nidification of Platalea leucorodia are discussed in this paper. Key words: Spoonbill, Platalea leucorodia, Nest and Nidification, Gudavi Bird Sanctuary, Shimoga. DOI: 10.3126/on.v7i1.2550 Our Nature (2009) 7:26-31